Learning by Transforming: Widening Access to Complex Circular Economy Science using Experimental Design - Barrios-O’Neill, Danielle; Ribul, Miriam; Tommencioni Pisapia, Chiara; Yan, Yiru; Rungta, Devanshi; Selby, Laura; Ren, Xinyi; Quintana, Claudio; Morrow, Roberta; Lanot, Alexandra; Baurley, Sharon; McQueen-Mason, Simon (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper presents a pilot pedagogical project exploring the potential of experimental design methods to engage students with complex scientific concepts, by focusing on translating these concepts specifically for a public audience. Conducted within the UKRI-funded Textiles Circularity Centre (TCC) at the Royal College of Art, the project tasked design students with designing an experience that can communicate the science of biobased textile recycling, an emerging circular economy process that is complex and typically inaccessible for laypeople. Framed as a process of translation rather than mastery, the project integrated interdisciplinary, multisensory, and speculative design and teaching methods to engage with a range of ways of conceptualizing and communicating complex science to a diverse audience. Students worked closely with scientific researchers, engaging with scientific materials and techniques, including enzymatic recycling and bacterial cellulose production. Through iterative development, the students produced Catalyst, a multisensory installation that employs tactile interaction, visual displays, and soundscapes to create an interactive material simulation of biobased recycling. The study identifies three key pedagogical outcomes with potential for application in wider contexts: enhanced technical comprehension, emotional engagement, and learner agency. We discuss the relationship of multimodal design methods to whole-systems thinking and learning. We propose that interdisciplinary, multisensory methods for enhancing complexity-oriented learning and public engagement, and raise possibilities to scale the model to other contexts that involve communication of complex information, as it may be able to activate new forms of learning and public engagement.